2017
DOI: 10.1021/acs.jafc.6b05147
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Lipopolysaccharide-Induced Neuroinflammation by Morin via MAPK, PI3K/Akt, and PKA/HO-1 Signaling Pathway Modulation

Abstract: Morin is a flavonoid isolated from certain fruits and Chinese herbs and is known to possess various medicinal properties. In this study, we investigated the anti-inflammatory effects of morin on lipopolysaccharide (LPS)-induced microglial activation, both in vitro and in vivo. We found that morin inhibited inducible nitric oxide synthase (iNOS) and pro-inflammatory cytokines in LPS-stimulated BV2 microglial cells. Furthermore, morin suppressed the microglial activation and cytokine expression in the brains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 48 publications
3
52
0
Order By: Relevance
“…A number of in vitro models, including microglia cell lines, stem cell derived microglia cultures, and primary dissociated cell cultures, were performed in order to study the role of microglia in neurodegenerative disorders and, in particular, relevant to PI3K signaling (for more detail, see [73]). This anti-inflammatory beneficial effect could be linked to the ability of inhibiting PI3K/Akt signaling pathways [74,75].…”
Section: Pi3k Role In Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of in vitro models, including microglia cell lines, stem cell derived microglia cultures, and primary dissociated cell cultures, were performed in order to study the role of microglia in neurodegenerative disorders and, in particular, relevant to PI3K signaling (for more detail, see [73]). This anti-inflammatory beneficial effect could be linked to the ability of inhibiting PI3K/Akt signaling pathways [74,75].…”
Section: Pi3k Role In Neuroinflammationmentioning
confidence: 99%
“…Morin, a flavonoid, exerts anti-inflammatory effects by downregulating MAPK and PI3K/Akt signaling pathways and upregulating the anti-inflammatory PKA/CREB and Nrf2/HO-1 pathways in microglia [75]. Furthermore, TGF-1α, an anti-inflammatory molecule, protects brain by repressing the overactivation of microglial cells via inhibition of PI3K and its downstream signaling molecules [123].…”
Section: Therapeutic Strategies On the Modulation Of Pi3k Signalingmentioning
confidence: 99%
“…Our finding showed that pretreatment with methylene blue at a subeffective, abolished the effect of morin on locomotion. Although we cannot completely rule out the possibility that other isoforms of NO synthase‐dependent mechanisms may underlie the psychotropic effect of morin (Ben‐Azu et al, 2019; Jung et al, ), this finding further implicates the role of l ‐arginine‐NO pathways and also suggests that nNOS isoform is involved in the effect of morin. Together, this finding and other investigations confirm that modulation of the neuronal isoform of NOS is critical for the central effects of NOS inhibitors on locomotion (Haj‐Mirzaian et al, ; Vale, Green, Montgomery, & Shafi, ; Volke et al, ).…”
Section: Discussionmentioning
confidence: 81%
“…Morin is a neuroactive polyphenolic compound obtained from mulberry leaves (Kapoor & Kakkar, ). Previous preclinical investigations have reported that morin demonstrated immunomodulatory and antineuroinflammatory (Jung et al, ; Ola et al, ), antioxidant (Ola et al, ), antidiabetic (Ola et al, ), antixanthine (Yu, Fong, & Cheng, ), antihypertensive (Prahalathan, Saravanakumar, & Raja, ), and anticancer (Zhang et al, ) properties. Recent studies have also shown that morin produces antidepressant (Ben‐Azu et al, ), antipsychotic (Ben‐Azu, Aderibigbe, Omogbiya, Ajayi, & Iwalewa, ; Ben‐Azu et al, ; Ben‐Azu, Aderibigbe, Eneni, et al, ; Ben‐Azu et al, ), anxiolytic (Mangaiarkkarasi, Viswanathan, Ramaswamy, & Tharani, ), antiamnesic (Lemkul & Bevan, ), and anti‐Parkinsonia (Zhang et al, ) properties in behavioral paradigms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation